2019
DOI: 10.1088/1873-7005/aaf81a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of bubble changes in an oil film impacted by oil droplets via a coupled level set and volume-of-fraction method

Abstract: A coupled level set and volume-of-fraction method is applied to investigate the impact of an oil droplet on an oil film containing a bubble. Subsequently, the deformation of the bubble is analyzed. Simulation results show two different movement forms of bubbles after an oil droplet impacts an oil film under different impacting velocities: stable deformation and bubble breaks. Bubble breaks originate from the combined action of surface tension and viscous shear force. Oil film thickness also affects bubble defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…When the droplet touched the stationary leaf at 0 ms, the bottom of the droplet flattened and bubble capture occurred (0.2 ms) (Lee et al, 2012). At the initial impacting stage (0.6 ms), inertial force dominated and the upper part of the droplet remained spherical (Zhou et al, 2019). At 1.0 ms, the liquid at the droplet bottom expanded outward in a circular shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the droplet touched the stationary leaf at 0 ms, the bottom of the droplet flattened and bubble capture occurred (0.2 ms) (Lee et al, 2012). At the initial impacting stage (0.6 ms), inertial force dominated and the upper part of the droplet remained spherical (Zhou et al, 2019). At 1.0 ms, the liquid at the droplet bottom expanded outward in a circular shape.…”
Section: Resultsmentioning
confidence: 99%
“…At the initial impacting stage (0.6 ms), inertial force dominated and the upper part of the droplet remained spherical F I G U R E 3 Schematic diagram of the experimental setup. (Zhou et al, 2019). At 1.0 ms, the liquid at the droplet bottom expanded outward in a circular shape.…”
Section: Droplets Intercepted On Tea Leavesmentioning
confidence: 95%
“…Scientists with diesel hollow droplets used in internal combustion engines simulated the changes on the hollow and its effects on impact with the piston (Sedighi et al 2010). The researchers numerically modeled the height of the jet when a hollow impact with various Reynolds and Weber numbers with a substrate (Zhou et al 2019). Experimental studies were performed for hollow glycerin drop at different temperatures, which increased the dispersion rate and altitude of the jet with increasing temperature (Basu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was established that droplets can be coalesced by applying voltages with opposite sign across the two droplets during their merging and there exists a strong attraction to each other whenever they are in close proximity (Link et al 2006). The coalescence based merging of droplets has been achieved by means of physical impact as well as under the influence of electric field (Chabert et al 2005, Zhou et al 2019. Zhou et al (2019) numerically investigated the impact of an oil droplet on an oil film containing a bubble through coupled level set and volume-of-fraction method.…”
Section: Introductionmentioning
confidence: 99%
“…The coalescence based merging of droplets has been achieved by means of physical impact as well as under the influence of electric field (Chabert et al 2005, Zhou et al 2019. Zhou et al (2019) numerically investigated the impact of an oil droplet on an oil film containing a bubble through coupled level set and volume-of-fraction method. Baroud et al (2010) and Christophe et al (2009) reported that the merging of droplets is solely driven by interfacial tension between the participating phases and the phenomena can be realized by the instability of the leading interface of the droplet.…”
Section: Introductionmentioning
confidence: 99%